Outcome of Treatment of Displaced Intrartcular Fracture Calcaneus by Plate and Screws - Shwan Mohammed Mustafa; Las Jamal hwaizi (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2018)
Background: Management of calcaneal fractures has always been in controversy. Many treatment techniques have been described. In this prospective study, we studied the functional outcome of surgically treated intra-articular calcaneal fracture.  Aim of study: To study the functional outcomes and complication in the surgically managed calcaneal fracture.  Patient and Methods: A total of 24 Patients with 26 calcaneal fractures operated in west emergency and Erbil teaching hospital over a period of 18 months (January 01, 2016 to August 01, 2017) were included in the study, Pre-operative computed tomography (CT) scans carried out in all patients. Maryland foot score was used to evaluate to assess the functional outcome and study complication.  Results: Twenty-four patients (22 unilateral and 2 bilateral), mean follow up 18 month, the mean age being 35.41 years (range 18-60 years), consisting of 3(12.5%) female and 21(87.5%) male were included in the study. Most common mode of injury was fall from height in 23(95.8%) patients, while road traffic accident was in 1(4.16%) patients. Three patients had associated spinal injuries. Results according to Maryland foot score were excellent in 25%, good in 62.5%, and none of the patients had poor results. Complications include synovitis, broadening and superficial infection.  Conclusion: ORIF with restoring the articular congruity with low profile locking plate is the ideal treatment for joint depression type and Sanders Type II/III and IV. Even Sanders Type IV (which was thought to be associated with poor results) had a good outcome in short-term follow-up. Use of proper surgical timing/technique/under aseptic precaution can lead to good or excellent results in more than 90% of patients and avoiding the majority of the complications. Thus ORIF in these patients should be encouraged.